Regulated plasmalemmal expansion in nerve growth cones (The Rockefeller University Press, 1991)
To study the mechanisms underlying plasmalemmal expansion in the nerve growth cone, a cell-free assay was developed to quantify membrane addition, using ligand binding and sealed growth cone particles isolated by subcellular fractionation from fetal rat brain. Exposed versus total binding sites of 125I-wheat germ agglutinin were measured in the absence or presence of saponin, respectively, after incubation with various agents. Ca2(+)-ionophore A23187 in the presence of Ca2+ increases the number of binding sites (Bmax) but does not change their affinity (KD), indicating that new receptors appear on the plasma membrane. Similarly, membrane depolarization by high K+ or veratridine significantly induces, in a Ca2(+)-dependent manner, the externalization of lectin binding sites from an internal pool. Morphometric analysis of isolated growth cones indicates that A23187 and high K+ treatment cause a significant reduction in a specific cytoplasmic membrane compartment, thus confirming the lectin labeling results and identifying the plasmalemmal precursor. The isolated growth cones take up gamma-amino-butyric acid and serotonin, but show no evidence for Ca2(+)-dependent transmitter release so that transmitter exocytosis is dissociated from plasmalemmal expansion. The data demonstrate that plasmalemmal expansion in the growth cone is a regulated process and identify an internal pool of precursor membrane.